A Phase Transition of the Unconscious: Automated Text Analysis of Dreams in Psychoanalytic Psychotherapy - Gennaro, Alessandro; Kipp, Sylvia; Viol, Kathrin; de Felice, Giulio; Andreassi, Silvia; Aichhorn, Wolfgang; Salvatore, Sergio; Schiepek, Günter (Frontiers in Psychology, 2020)
Aim. Psychotherapy could be interpreted as a self-organizing process which reveals discontinuous pattern transitions (so called ‘phase transitions’). Whereas this was shown in the conscious process of awake patients by different measures and at different time scales, dreams came very seldom into the focus of investigation. The present work tests the hypothesis that, by dreaming, the patient gets progressively more access to affect laden (i.e. emotionally-charged) unconscious dimensions. Furthermore, the study investigates if, over the course of psychotherapy, a discontinuous phase transition occurs in the patient’s capacity to get in contact with those unconscious dimensions. Methods and Procedures. A series of 95 dream narratives reported during a psychoanalytic psychotherapy of a female patient (published as the “dreams of Amalie X”) was used for analysis. An automated text analysis procedure based on Multiple Correspondence Analysis was applied to the textual corpus of the dreams highlighting a 10 factors structure. The factors, interpreted as affective-laden unconscious meaning dimensions, were adopted to define a 10-dimensional phase space, in which the ability of a dream to be associated with one or more local factors represent complex affective-laden meanings is measured by the Euclidian Distance (ED) from the origin of this hyper-space. The obtained ED time series has been fitted by an ARIMA model and by nonlinear methods like Dynamic Complexity, Recurrence Plot, and Time Frequency Distribution. Change Point Analysis was applied to these nonlinear methods. Results. The results show an increased frequency and intensity of dreams to get access to affective laden meanings. Nonlinear methods identified a phase transition-like jump of the ED dynamics onto a higher complexity level of the dreaming process, suggesting a nonlinear process in the patient’s capacity to get in contact with unconscious dimensions. Conclusion. The study corroborates the hypothesis that, by dreaming, the patient gets progressively more access to affect laden meaning intended as unconscious dimensions. The trajectory of this process has been reproduced by an ARIMA model and, beyond this, nonlinear methods of time series analysis allowed the identification of a phase transition in the unconscious process of the psychoanalytic therapy under investigation.